Reflection of experiences with academic supervisors, supervisees and issues of power - Odularu, O. I.; Akande, J. O. (South African Journal of Higher Education, 2024)
Academic supervision is essential for developing students’ careers and educational advancement. The systematic review approach was chosen for the methodology of this study. It has been observed in the literature that there are positive and negative experiences between supervisees and their supervisors. This led to the research gap in the study, which stated that supervisors and their supervisees are inadequately prepared for their roles. The study addressed these gaps through a systematic review of the article sub-topics. The conceptual model was adopted for this article, and it articulates how supervisors can exhibit their dispositional qualities. Additionally, this article recommends enhancing creative and innovative research to intensify a sense of autonomy and periodically updating research instructions on actualising the vision and mission statements of Higher Educational Institutions (HEIs). The study further recommends that training initiatives for supervisors should be encouraged in HEIs through academic research groups, among others.